Adsorption of iron by using hybrid Akar Putra and commercialized chicken eggshells as bio-sorbents from aqueous solution - H.M. Nasir; A. Azmi; A.Z. Aris; S.M. Praveena (Global Journal of Environmental Science and Management)
Heavy metal contamination in the environment could cause harmful effects both to human health and aquatic life. Numerous remediation methods had been developed to encounter with the contamination problem prior to degrade, decrease and to purify the contaminated water at minimal concentration as low as possible. Therefore, in current study, commercialized chicken eggshells and hybrid Akar Putra chicken eggshells were conducted in batch experiment to testify the capabilities of bio-sorbent materials in iron (II) ion removal from aqueous solution at optimized level of dosage and equilibrium contact time. The optimum condition for iron (II) removal for commercialized chicken eggshells and hybrid Akar Putra chicken eggshells bio-sorbents reached at 0.30 g with optimum contact time of 50 minutes and 91.83% and 91.07% of removal percentage with 0.60 g at 40 minutes. The final concentration from both bio-sorbents is achieved below than drinking water guideline (0.30 mg/L), 0.1635 mg/L and 0.1785 mg/L, respectively. The isotherm adsorption results showed it fitted better in Langmuir Isotherm Model than in Freundlich Isotherm Model, however with weak bonding, which could not held onto the heavy metal ions in long time period. In brief, commercialized chicken eggshells and hybrid Akar Putra chicken eggshells have considerable potential in removing heavy metal in aqueous solution. The selection of the bio-sorbent materials is more favorable as it reduces dependency towards chemical usage in water treatment which could have complied with drinking water guideline that can be obtained easily, abundance in amount, cheap and biodegradable.